Theology and the boundary discourse of human rights - Regan, Ethna (Georgetown Univ. Press, 2010)
Introduction -- A dialectical boundary discourse : secular and religious -- Are human rights historical? -- Are human rights universal? -- A dialectical boundary discourse of human flourishing -- The charter of the united nations -- The universal declaration of human rights -- Human rights and the Catholic Church since the Second Vatican Council -- Pope John Paul II and human rights -- The direction of Pope Benedict XVI -- A crisis of trust -- Theological anthropology and human rights : Karl Rahner's concentration on the human -- Theological engagement with human rights : four examples -- Imago dei : indicative and imperative -- Karl Rahner : a concentration on the human -- Human capacity for God : supernatural existential -- Human goodness : the anonymous Christian -- Human freedom -- Human experience and the experience of God -- Human dignity -- Human suffering -- Human rights in time -- Realism between memory and hope -- Memory -- The ethics of memory -- Trials and truth commissions : just memory -- Towards just memory : a Guatemalan case study -- Theology towards just memory : the haunted tardiness of Johann Baptist Metz -- The influence of Karl Rahner -- Political theology -- Memory : dangerous memory -- Narrative : dangerous stories -- Solidarity : dangerous responsibility -- Auschwitz : an interruption that orients -- Challenge : a future based on the memory of suffering -- Silence and interruptive realism -- Liberation theology and human rights : from interruptive realism to the centrality of La realidad -- Liberation theology and human rights -- The preferential option for the poor -- Who are the poor? -- The rights of the poor -- A mysticism of human rights -- From interruptive realism to the centrality of La realidad -- The weight of reality : Ignacio Ellacuría -- Rights-holders or beggars : responding to the post-liberal critique -- Disdain for the secular : the refusal of a rival -- A preference for a theological politics over political theology -- Impatience with the provisional